Towards a Model of Electrochemical Immunosensor Using Silver Nanoparticles. (2017) - Felici, Sara; Lavecchia, Teresa; Angjellari, Mariglen; Micheli, Laura; Orlanducci, Silvia; Terranova, Maria Letizia; Palleschi, Giuseppe
Abstract: This work deals with the use of silver nanoparticles, to produce an electrochemical enzymeless probe. Silver nanoparticles play the dual role of markers for electrochemical measurements and support of an immunological chain for immunoglobulin (IgG). AgNPs are synthesized by modifying the Brust method in terms of time and amount of reagents. The interaction between the antibody (Ab) and silver nanoparticles, is then monitored through UV-VIS spectroscopy following the plasmonic shift of AgNPs, and electrochemically by cyclic and anodic stripping voltammetries as the presence of Ab modifies the electrochemical behavior of silver nanoparticles. The determination of the specific analyte, targeted by the Ab, immobilized on silver nanoparticles, is followed by the anodic stripping of the metal nanoparticles. This technique demonstrates that the peak area of the oxidative signal corresponding to the stripping of Ag to Ag + ions decreases while increasing the IgG presence on silver nanoparticles.